Role of women in disaster risk governance. (2018) - Hemachandra, Kinkini; Amaratunga, Dilanthi; Haigh, Richard
Abstract: Since the frequency and magnitude of occurrence of natural hazards increased unprecedented within this century, policy makers, researchers and practitioners have endorsed on innovative disaster risk reduction measures towards enhancing resilience. In achieving this, disaster risk governance promotes innovative and accountable approaches enhancing their effectiveness. Multi-stakeholder engagement is a fundamental element of disaster risk governance. Many international strategies and frameworks have identified women as one of the key stakeholders in any disaster management efforts due to many reasons. Women play a significant role in disaster response and recovery stages specifically at household level. However, their roles in organizational decision making, particularly in disaster risk governance, is limited due to uncovered reasons. This has created equity and equality issues among one of the most affected communities from hazards. Therefore, this novel study attempts to explore and emphasise the role of women in disaster risk governance, risk governance efforts and to uncover the barriers that limit their role in disaster risk governance. Hence, the study conducted a substantial level of literature review. Accordingly, it reveals that the role of women in disaster risk governance as vital for an effective disaster risk governance and resilience. Further, the study identified socio-cultural factors, individual characteristics, legal and institutional factors and socio-economical factors as the barriers that limit their role in disaster risk reduction and disaster risk governance efforts.